2020
DOI: 10.1155/2020/4612376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Control on a Specific Electromagnetic Micromirror

Abstract: In this paper, 10 resonant modes were divided based on the structure of a specific two-dimensional electromagnetic micromirror from Professor Shen’s team and Finite Element Method (FEM), and using as many as 10 resonant modes to do such analysis was the first time according to the best of our knowledge. The results showed that the slow axis can participate in several resonant motions under the signals of resonant frequencies. In particular, participating in Mode 1 for slow-scan axis was the key reason to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For comparison, the secondary filtering approach developed in Ref. 8 is also used to suppress the influence of noise on the output measurement of EMM. Figure 11 shows the corresponding filtering result of the secondary filter in time-domain.…”
Section: Modeling and Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, the secondary filtering approach developed in Ref. 8 is also used to suppress the influence of noise on the output measurement of EMM. Figure 11 shows the corresponding filtering result of the secondary filter in time-domain.…”
Section: Modeling and Simulation Resultsmentioning
confidence: 99%
“…However, specifying the optimal gains for PID controller is not an easy task since the optimization procedure, in this case, is a nonconvex problem. In our previous work 8 , it is shown that the slow-scanning axis in the EMM system participated in several resonant motions under the signals of resonant frequencies, especially in the resonant movement on the slow-scanning axis shown in Fig. 2 , which was the main reason of the instability in the control of electromagnetic micromirror.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Now two aspects are focused on to show the performance of the advanced extremum seeking scheme. Compared with the secondary filtering [8] (seen in Fig. 9 and Fig.…”
Section: A Second Order Model In Slow-scan Axis Controlmentioning
confidence: 99%
“…PID control and a low pass filter (LPF) were proposed in Han's research [7], but choosing appropriate gains for PID controller is very difficult to manage and the rings from driving coils were difficult to be eliminated. In our previous work [8], it showed that the slow axis in electromagnetic micromirror system participated in several resonant motions under the signals of resonant frequencies, especially in the resonant movement on slow-scan axis shown in fig. 1, which is the main reason of the instability in the control of electromagnetic micromirror.…”
Section: Introductionmentioning
confidence: 97%